Conference on Lasers and Electro-Optics 2019
DOI: 10.1364/cleo_si.2019.sf2h.4
|View full text |Cite
|
Sign up to set email alerts
|

Reversible Switching of Optical Phase Change Materials Using Graphene Microheaters

Abstract: Reconfigurable photonic systems featuring minimal power consumption are crucial for integrated optical devices in real-world technology. Current active devices available in foundries, however, use volatile methods to modulate light, requiring a constant supply of power and significant form factors. Essential aspects to overcoming these issues are the development of nonvolatile optical reconfiguration techniques which are compatible with on-chip integration with different photonic platforms and do not disrupt t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
13
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1
1
1

Relationship

4
5

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 82 publications
1
13
0
Order By: Relevance
“…Based on the optimized heater design, Fig. 2c maps the average heater temperature for different pulse duration and voltage combinations, and the results (550 -630 K for crystallization and 1020 K for amorphization) are in excellent agreement with our prior data 42,50 .…”
Section: Electrothermal Switching Device Platformsupporting
confidence: 78%
See 1 more Smart Citation
“…Based on the optimized heater design, Fig. 2c maps the average heater temperature for different pulse duration and voltage combinations, and the results (550 -630 K for crystallization and 1020 K for amorphization) are in excellent agreement with our prior data 42,50 .…”
Section: Electrothermal Switching Device Platformsupporting
confidence: 78%
“…As an example of phase and wave front control, we further realized active switching of a Huygens' surface beam deflector using the platform. Moreover, the electrical switching design and the geometric optimization approach for large-aperture metasurfaces demonstrated herein are also transferrable to other emerging heater materials such as silicon 56,57 and graphene 50 to enable a diverse array of reconfigurable metasurface devices.…”
Section: Resultsmentioning
confidence: 98%
“…We have recently demonstrated highly consistent electrothermal switching of GSST over 1,000 phase transition cycles using on-chip metal micro-heaters 44 . Additionally, reversible switching of GSST and other phase change materials using transparent graphene and doped Si heaters have also been validated [57][58][59] . In this regard, the use of GSST rather than the classical GST alloy uniquely benefits from not only GSST's low optical attenuation but also its improved amorphous phase stability.…”
Section: Discussionmentioning
confidence: 98%
“…In a pioneering work, Rios et al demonstrated a hybrid framework incorporating a graphene heater to electrothermally switch a large area of GSST [231]. Minimal optical loss, high intrinsic in-plane thermal conductivity, low heat capacity, and scalability make graphene a potential candidate for efficient conversion of PCMs in reconfigurable PICs.…”
Section: Integrated Phase-change Photonic Switches and Modulatorsmentioning
confidence: 99%